Facile process for ammonia sensing using electrospun polyvinylidene fluoride/polyaniline (PVDF/PANI) nanofibers chemiresister - Kondawar, Sanchit; Late, Dattatray J.; Anwane, Rajashree S.; Kondawar, Subhash B.; Koinkar, Pankaj; Parinov, Ivan A. (Advanced Materials, 2019)
Electrospun polyvinylidene fluoride/polyaniline (PVDF/PANI) nanofibers chemiresister was fabricated by electrospinning and polymerization. As-fabricated PVDF/PANI nanofibers chemiresister was characterized by SEM, FTIR, TGA and DTG analyses. Cost effective with high accuracy microcontroller based sensor set up was designed for the measurement of change in resistance of chemiresister with respect to different concentrations of ammonia gas at various temperatures. The semiconducting behavior of the chemiresister was found to respond quickly towards ammonia gas. High sensitivity, fast response and recovery of PVDF/PANI nanofibers for ammonia gas at room temperature confirmed the chemiresister as potential candidate for ammonia sensing in environmental monitoring safety systems, chemical and automotive industries.